PENGARUH GAYA KEPEMIMPINAN HUKUM TUA TERHADAP KEBERHASILAN PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DI DESA KAUDITAN SATU KECAMATAN KAUDITAN - Mewengkang, Norma (Sam Ratulangi University, 2014)
Abstract: both the bad governance will appear on good governance; generally the implementation of theprinciples of good governance has not been implemented properly. This research is to know how theleadership style of village head of Kauditan One in governanceThis research method is a survey research. Data Collection Techniques through interview questionnaires,and field observations Data analysis techniques used are quantitative analysis with parametric / inferentialstatistical analysis. The total number of respondents / informants in this research is 66 people, consistingof village government apparatus 26 people and community members 40 peopleSimple regression analysis and simple correlation analysis show that Old Law leadership style hassignificant relation and influence toward applying the principles of good governance in the administrationof village administration 43,97% at test level a = 0,01 or level of trust / belief equal to 99 %, as indicated bythe test result with the t-test where the t-value of 7.09 turns out to be greater than the list at the significantlevel of 0.01 (1%) with the degree of free (sb) 64 which is only 2.39 :Keywords: leadership style, village head and good governance